Toleransi Beragama Berbasis Kearifan Lokal di Pulau Lombok Nusa Tenggara Barat - Subhan Abdullah Acim; Rahman Rahman (Jurnal Keislaman, 2023)
Tolerance is an effort made by religious people to respect each other and respect each other's beliefs. Lombok community with multicultural religion is very prioritizing the principle of tolerance through local wisdom. The approach used in this study is a qualitative approach with descriptive analysis method. The results of this study reveal that, local-based Tolerance conducted by religious people in Lombok as shown in the religious activities of the community that includes followers of other religions to participate in their religious practices. Such as Christmas, ' Eid, Vesak celebration, and other religious practices. Lombok's muslim community does not hesitate to invite their non-muslim neighbors to enliven the halal bi halal event, the Prophet's birthday and other celebrations, Hindus also invite their neighbors to enliven the ogoh-ogoh event which is their routine religious event, Christians also share and invite their neighbors to enliven their Christmas event. So that tolerance in the local wisdom of the people of Lombok is based on three aspects, namely solidarity, mutual cooperation, and deliberation. These three things are the local culture of the community that has been practiced for generations, in order to achieve a harmonious and orderly life.